2016
DOI: 10.1016/j.ceramint.2016.08.177
|View full text |Cite
|
Sign up to set email alerts
|

Fine-patterning of sol-gel derived PZT film by a novel lift-off process using solution-processed metal oxide as a sacrificial layer

Abstract: Sub-5µm pattern of sol-gel derived lead-zirconium-titanate (PZT) film with a thickness of 80-390 nm was successfully prepared on Pt(111)/TiO x /SiO 2 /Si (100) substrate by a novel lift-off process using solution-processed metal oxides as a sacrificial layer. The process is simply divided into three steps: In-Zn-O (IZO) sacrificial layer spin-coating and patterning, PZT film formation followed by lift-off process. The results suggested that the IZO layer is effective in preventing PZT crystallization because o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…ZnO and PZT films are usually used as piezoelectric layers in pMUTs [ 15 , 16 , 17 , 18 , 19 , 20 ]. Compared with that of PZT film the deposition process of ZnO film is simple and compatible with micromachining technology [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. In order to improve the properties of pMUT, Belgacem studied the influence of centred and ring top electrode on the coupling factor of pMUT with a circular piezoelectric composite diaphragm released by the expensive deep reactive ion etch (DRIE) process, and they found that when the PZT was removed outside the electrode this can improve the coupling factor [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…ZnO and PZT films are usually used as piezoelectric layers in pMUTs [ 15 , 16 , 17 , 18 , 19 , 20 ]. Compared with that of PZT film the deposition process of ZnO film is simple and compatible with micromachining technology [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. In order to improve the properties of pMUT, Belgacem studied the influence of centred and ring top electrode on the coupling factor of pMUT with a circular piezoelectric composite diaphragm released by the expensive deep reactive ion etch (DRIE) process, and they found that when the PZT was removed outside the electrode this can improve the coupling factor [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the feature size was mostly limited above 50 μm, and also PZT films exhibited random crystalline structure, large leakage current, and rather poor ferroelectric properties. Recently, Tue et al demonstrated sub-5 μm pattern of sol-gel-derived PZT films with a thickness of 80-390 nm by a novel lift-off process using solution-processed amorphous metal oxides as a sacrificial layer (Figure 13) [59]. The process includes three steps as follows: (1) deposition and patterning of the sacrificial lift-off layer (In-Zn-O), (2) PZT spin coating, and (3) etching of the sacrificial layer for PZT lift-off.…”
Section: Lift-off Processmentioning
confidence: 99%
“…AFM image of fine PZT pattern: (a) 2D morphology, (b) 3D morphology, and (c) local surface morphology[59].…”
mentioning
confidence: 99%